PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN KETERAMPILAN MERAJUT DALAM UPAYA PENINGKATAN PENDAPATAN KELUARGA - Masruroh, Nikmatul; Sadhie, Muhammad (Yayasan Sagita Akademia Maju, 2024)
This community service has the first goal, assistance in the process of developing knitting skills, second, assistance in community empowerment so as to increase family income. This service is carried out using the ABCD (Asset Based Community Development) method, namely service with the stages of finding, dreaming, designing, determining and doing. So that this service produces the first asset in the form of the ability to make knitting in the community developed with training and innovation of knitting products for PKK women, secondly providing socialization and awareness of the importance of increasing family income, thus collaborating in community empowerment so that knitting activities have an impact on family income. As a result, the development of this skill provides additional income for PKK mothers.